2017
DOI: 10.1063/1.4993917
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cu2–xSe platelets at grain boundaries and within grains in Cu(In,Ga)Se2 thin films

Abstract: Cu(In,Ga)Se2 (CIGS)-based solar cells reach high power-conversion efficiencies of above 22%. In this work, a three-stage co-evaporation method was used for their fabrication. During the growth stages, the stoichiometry of the absorbers changes from Cu-poor ([Cu]/([In] + [Ga]) < 1) to Cu-rich ([Cu]/([In] + [Ga]) > 1) and finally becomes Cu-poor again when the growth process is completed. It is known that, according to the Cu-In-Ga-Se phase diagram, a Cu-rich growth leads to the presence of Cu2–xSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…During the third stage of the three-stage growth process, the ratio of Cu=In decreases, and the CS secondary phase at the GBs might transform back to the CIS or CIGS phases. Nevertheless, such CS secondary phases are occasionally found at the GBs of bulk CIGS after a full three-stage growth [42], consistent with the present observation.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…During the third stage of the three-stage growth process, the ratio of Cu=In decreases, and the CS secondary phase at the GBs might transform back to the CIS or CIGS phases. Nevertheless, such CS secondary phases are occasionally found at the GBs of bulk CIGS after a full three-stage growth [42], consistent with the present observation.…”
supporting
confidence: 92%
“…FIG [40,41]. Occasionally, small platelets with Cu 2−x Se phases were found at GBs in Cu-poor CIGS [42]. Our results show that such topotactic transitions between CIS and Cu 2−x Se phases commonly exist near the CIS GBs when sufficient Cu diffuses into GBs.…”
mentioning
confidence: 61%
“…A depletion of Se and In as well as an enrichment of Cu, O, and Rb at the grain boundary is observed. Similar results (in studies without Rb) have been reported previously . But also contrary results have been published …”
Section: Resultsmentioning
confidence: 99%
“…1c). Recent high-resolution TEM evidence from Simsek Sanli et al 30 has revealed the presence of interspersed Cu 2 Se domains within CIGS grains, to which they attributed a topotactical grain growth effect during the three-stage process 31 . At this point, it is not possible to resolve with certainty which of the two scenarios occurs in reality.…”
Section: Cbd-zn(os)mentioning
confidence: 99%